Knowledge, Attitudes, and Perceptions of Dental Assistants regarding Dental Asepsis and Sterilization in the Dental Workplace - Syed Sarosh Mahdi; Zohaib Ahmed; Raheel Allana; Francesco Amenta; Daniyal Agha; Mohammad Wasay Latif; Umer Daood; Carina Mehanna (International Journal of Dentistry)
Aims and Objectives. This study aims to assess the knowledge, attitude, and perceptions of dental asepsis and sterilization among dental assistants in Pakistan. Materials and Methods. A cross-sectional study was carried out. A 27-item prepilot tested close-ended questionnaire was designed and administered online to collect data on knowledge of asepsis, sterilization, instrument handling, disinfection, hand-hygiene practices, dental practice, age, education, and experience level from March 2020 to June 2020. Results. Out of 70 dental assistants, the majority were aged between 21 and 29 years (44.30%), more than two-thirds (85.41%) of the dental assistants were working in a hospital, while 14.29% were working in private clinics, only 7.1% had a diploma in the dental assistant program, and 74% had more than 2 years of experience in practice. Dental assistants working in private practice (76.30) had a higher mean knowledge scores compared to those working in hospital (74.25), while those with less than 2 years of experience (75.61) had a higher scores compared to those with 2–5 years of experience (73.96). Conclusion. Better compliance with recommended infection control and waste management practices is needed for all dental assistants. Continuing education programs targeting such awareness are vital to improve the management of hazardous waste practices among dental assistants.